Genetic structure of ten Artemia populations from China: cumulative effects of ancient geological events, climatic changes, and human activities - Li, Ke; Zhang, Rui; Sui, Li-Ying; Zhang, Chi; Han, Xue-Kai (Frontiers in Marine Science, 2024)
This study investigated the population genetics and distribution patterns of Artemia populations from ten inland salt lakes in China. A total of 1,274,698 Artemia single nucleotide polymorphisms (SNPs) were identified. The results showed that these populations could be geographically and genetically divided into four distinct groups, and that the Tibetan populations were further divided into two subpopulations with a trend of decreasing genetic diversity from west to east. The Tibetan population had the highest genetic diversity, whereas the Shanxi population had the lowest. There was moderate genetic differentiation between the Tibetan populations and greater genetic differentiation between the Xinjiang and Shanxi populations. IBD (isolation by distance) suggested that geographical isolation contributes to genetic differentiation. In addition, there was some degree of gene flow among the ten populations, with A. sinica showing unidirectional gene flow in all populations in the eastern Nagri region. Species distribution modeling showed that mean annual temperature, temperature seasonality, and annual precipitation were the main environmental factors affecting the distribution of Artemia populations and suitable habitats for Tibetan populations will be further reduced in the future. It is necessary to strengthen the protection of germplasm resources and formulate scientific protocols for the sustainable development and utilization of Artemia resources.